Rio+20, biodiversity marginalized. Issue 1 (8th October 2012) - Carrière, Stéphanie M.; Rodary, Estienne; Méral, Philippe; Serpantié, Georges; Boisvert, Valérie; Kull, Christian A.; Lestrelin, Guillaume; Lhoutellier, Louise; Moizo, Bernard; Smektala, Georges; Vandevelde, Jean‐Christophe
Abstract At the Rio+20 Conference (June 2012), the biodiversity conservation agenda was subsumed into broader environmental issues like sustainable development, "green economy, " and climate change. This shoehorning of biodiversity issues is concomitant with a trend toward market‐based instruments and toward standardized biodiversity assessment and monitoring. This article raises concern that these trends can marginalize important and specific aspects of biodiversity governance, including other policy tools and region‐specific socio‐ecological environments. Among other trends, this contributes to the marginalization of agroecosystems as habitat and matrix for biodiversity. Such agroecosystems, however, can have a major impact on conservation outcomes as they comprise a major part of terrestrial lands. If the biodiversity crisis is to be curbed, special attention must be drawn to societies, institutional approaches, and environments that are currently marginalized in conservation policies.